EARLY POSTOPERATIVE COMPLICATION FOLLOWING FILTRATION SURGERY IN DR. KARIADI GENERAL HOSPITAL SEMARANG 2020-2022 - Mazidah Zulfa, Mazidah Zulfa; Puspasari, Denti; Rahmi, Fifin L. (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: Filtration surgery is the most frequent surgery in managing glaucoma. Although trabeculectomy is generally a safe and effective procedure, complications can occur. The purpose of the study was to describe the early postoperative complications in patients who had undergone filtration surgery. Methods: This study was a retrospective study that uses secondary data from electronic medical records of patients who had filtration surgery between January 1, 2020, and December 31, 2022, in Kariadi Hospital Semarang. Preoperative data include age, gender, visual acuity, intraocular pressure, and type of glaucoma. The incidence of early postoperative complications was described up to 3 weeks of follow-up. Results: 287 eyes were obtained from 266 patients who underwent filtration surgery. 168 eyes (58.5%) had phaco-trabeculectomy, 117 eyes (40.77%) had trabeculectomy and 2 eyes (0.7%) had ECCE-trabeculectomy. Primary angle closure glaucoma (126 eyes, 43.9%) was the most common type of glaucoma treated with filtration surgery. During the 3-week follow-up period, 93 eyes (32.4%) experienced an early complication with trabeculectomy being more common (17.42%) than combined surgery. The commonest complication found was hypotony in 69 eyes (24%). Other complications include hyphema (3.14%), transient intraocular pressure elevation (3.14%), bleb leakage (2.09%), suprachoroidal haemorrhage (0.7%), subhyaloid haemorrhage (0.35%) and retinal haemorrhage (0.35%). Conclusion: This study found the most common early postoperative complication of filtration surgery was hypotony. This complication occurs frequently after trabeculectomy.